Growth and influence of industrial schools - Thackrey, John Eugene (My University, 1893)
Introduction: The industrial school system is one of those promising and already influential institutions that have sprung up in this nineteenth century. Before the beginning of this century there were trades-schools, schools of special sciences, etc but none of these were what we now call industrial schools or colleges. These we may say are mostly American, for, though all other civilized countries have schools for all the trades, sciences, and arts, each school has its special class of students and all are more or less special or technical in their nature. Their object is more to train skilled specialists than to give a good general education that will serve as a good foundation for any kind of pursuit. They are not based on the broad fundamental principles of our American schools which train the mind as well as the hand and make citizens as well as skilled workman.
Citation: Thackrey, John Eugene. Growth and influence of industrial schools. Senior thesis, Kansas State Agricultural College, 1893.
Morse Department of Special Collections
Keywords: Industrial; School; Specialist; Pursuit; Theses; Manuscripts (documents)